Modelo experiencial en la construcción de conocimiento en los niños de inicial 2 de la Unidad Educativa Intercultural Bilingüe Totoras De La Comunidad Totoras, parroquia Achupallas cantón Alausí provincia de Chimborazo en el período 2017-2018 - Yautibug Guacho, Luis Freddy (2018)
The present research work consists of being able to determine how an experiential model can influence the construction of knowledge in the children from preschool II of the Unidad Educativa Intercultural Bilingue Totoras. It will be based on determining how this experiential model should be applied to children so that all of them can build their knowledge from an early age and thus be able to help throughout their academic life. The methodology is of qualitative order to be applied the observation sheet and the survey. It could be verified that the lack of application of new educational models does not achieve a satisfactory fulfillment since the experiential model tries to develop that people can learn from their own experience and be able to form their knowledge. This model could not be shown to satisfaction in children since this model must be structured in several cycles to understand how this method of learning works, from this root, was born this research work, how to achieve the children from preschool II can build his knowledge through this educational model (experiential model). Thus, after having applied the present research work, children could be adapted to this new model of education, this being a method that allows us a permanent interaction, a child can have contact between the action and the reflection of the act that is doing which will favor the child not only see things from a single point. Allowing to expand the possibilities of building knowledge valuing the own wisdom.